Sensitivity of modelled passive margin stratigraphy to variations in sea level, sediment supply and subsidence - Schmelz, William J.; Miller, Kenneth G.; Mountain, Gregory S.; Steckler, Michael S.; Browning, James V. (Basin research, 2024)
We produced a 10 Myr synthetic stratigraphic section using a forward stratigraphic model that generates marine deltaic stratigraphy over geological timescales. We recursively fit the model using a Bayesian inversion algorithm to test: (1) if it could be accurately reconstructed; (2) if the parameters used to create it could be recovered; and (3) the sensitivity of the model output to given model parameters and the attendant physical processes. The original synthetic stratigraphic section was produced with cyclical sea‐level variations of 40 and 30 m with 2.4 and 10 Myr periods respectively. Sediment was also supplied cyclically, in 2.4 and 10 Myr cycles with amplitudes of 30 and 80 tons/100 kyr, respectively, varying from a mean of 232 tons/100 kyr. Parameter values were sampled to fit the model using a Markov chain Monte Carlo algorithm, resulting in a ±5 m (1σ) variation between the experimental output and the original. Sea level varied by ±7 m (1σ) within the posterior distribution of parameters. As a result, both the 10 Myr and 2.4 Myr sea‐level cycles could be extracted from the original output. The variation in sediment supply was approximately ±38 tons/100 kyr (1σ) and, as a result, only the larger long‐term supply variations could be accurately recovered in refitting the model. The variation in thermal, flexural and total subsidence across those parameter sets is less than ±10 m (1σ). The original section experienced 150 m of total subsidence at the depocentre. Our results demonstrate the distinct and interpretable imprint of sea level and subsidence on continental margin stratigraphy can be quantified. Moreover, we conclude that sea‐level change produces a defined effect on the geometries of stratigraphic architecture, and that techniques applied for the purpose of delineating sea‐level variation from continental margin strata have a well‐founded conceptual basis. Modelledstratigraphy reconstructed using Bayesian inversion. The top panels show the reconstructedstratigraphy (panel a) and a wheeler diagram of this model output (panel b). Thethree other panels show the original and reconstructed values of: 1) flexure,thermal subsidence, and total subsidence (panel c); 2) sea‐level change (paneld); and 3) sediment supply variations (panel e). The greater variability in theposterior distribution of sediment supply values relative to those for sealevel suggests that the development of passive continental margin stratigraphic architecture is particularlysensitive to sea‐level variation.